Local approach to fracture applied to the analysis of a full size test on a pipe containing a girth weld defect. (December 2017) - Soret, Clément; Madi, Yazid; Gaffard, Vincent; Besson, Jacques
Abstract: A welded pipeline segment containing a girth weld defect is tested under combined internal pressure and bending. The test is then analyzed with respect to both overall elasto-plastic behavior and crack propagation up to failure. The analysis is carried out using the finite element method. Constitutive equations for the plastic behavior of both weld metal and base metal are determined using tests carried out on smooth and notched bars. The cracking behavior of the weld metal is characterized using SENT specimens. The detailed analysis of the test allows to better understand boundary conditions and to represent the pipe overall behavior. The GTN model is used to represent damage growth up to failure in the weld metal. The simulation then allows representing the pipe behavior up to failure due to through thickness crack propagation. Highlights: A full size test on a welded pipe carried out under internal pressure and bending Comprehensive material characterization including plasticity and ductile damage A computational strategy to simulate crack advance in the full size pipe up to failure